Efektivitas Pelaksanaan Program Pembinaan Dan Pendidikan Anak Tunagrahita Di SLB-C Yayasan Pembinaan Anak Cacat Di Kota Medan - Ririn Novita Sari (Welfare StatE, 2013)
Child of tunagrahita that is child having intellegence under average of normal child in general and have resistance in the field of adjustment and social interaction. This reality have child of tunagrahita not easy for parent, especially if faced by parent which less the understanding to all problems of child of tunagrahita. According to data steming from Body Centering Statistic ( BPS), amount of disabled peoples in indonesia in the year 2010 are equal to 2.126.785 souls. Blind 778.084 soul, tunarungu articulation of 267.974 soul, tunadaksa 733.740 soul, and tunagrahita 345.815 soul. Provinsi North Sumatera there are amount of disabled peoples in the year 2010 are 118.603 souls, consist of blind 43.390 soul, tunarungu articulation of 14.943 soul, tunadaksa 40.918 soul, and tunagrahita 19.284 soul. Pay attention to this problem, governmental for the agenda of mengentaskan prosperity of social of disabled peoples formulate various policies one of them educations and constructions programs for child of tunagrahita through panti or managed by institutions is public or government professionally. The purpose of this study was to determine the extent of the effectiveness of training programs and education in mental retardation SLB-C Foundation for Development of Disabled Children in Medan. Type of research used in this research is descriptive method. Meanwhile, the techniques of data analysis in this study using a single table and explained qualitatively by Likert scale. The conclusions obtained through analysis of the data that the The Effectiveness Implementation of Coaching Program and Education child's mental retardation In SLB-C Foundation for Disabled Children Coaching In Medan City is effective. The calculation result is effective viewed from several measurements that have been made, from the understanding of the program as much as 0.36, 0.675 as targets of accuracy, timeliness as of 0.45, from 0.91 as the goals and of real change as 0,78. Keywords: Effectiveness, Program Development and Education, Tunagrahita